2012
DOI: 10.1177/1087054712465335
|View full text |Cite
|
Sign up to set email alerts
|

AULA—Advanced Virtual Reality Tool for the Assessment of Attention

Abstract: Obtained normative data are relevant for the use of AULA for evaluating attention in Spanish children and adolescents in a more ecological way. Further studies will be needed to determine sensitivity and specificity of AULA to measure attention in different clinical populations. (J. of Att. Dis. 2016; 20(6) 542-568).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 25 publications
3
88
0
3
Order By: Relevance
“…When analyzing specific tasks, in the X-task, both visual correct answers (m boys = 25.18 vs. m girls = 39.70; U = 154.5; p < .01) and visual commissions (m boys = 32.82 vs. m girls = 18.30; U = 154.5; p < .01) showed significant differences in favor of girls. These results match to some extent those found for the general population in the normative study of the AULA (Iriarte et al, 2012), where it was found a general pattern of gender differences showing a trend to faster answers (both correct and incorrect) for boys in most of the age groups, as well as greater motor activity.…”
Section: Differences By Gendersupporting
confidence: 88%
See 1 more Smart Citation
“…When analyzing specific tasks, in the X-task, both visual correct answers (m boys = 25.18 vs. m girls = 39.70; U = 154.5; p < .01) and visual commissions (m boys = 32.82 vs. m girls = 18.30; U = 154.5; p < .01) showed significant differences in favor of girls. These results match to some extent those found for the general population in the normative study of the AULA (Iriarte et al, 2012), where it was found a general pattern of gender differences showing a trend to faster answers (both correct and incorrect) for boys in most of the age groups, as well as greater motor activity.…”
Section: Differences By Gendersupporting
confidence: 88%
“…During the No-X task, which is intended to generate an overstimulation, there are nine distractors, with a sequence that alternates two visual, three auditory, and four combined distractors; on the contrary, during X-task, thought to generate hypoactivation, there are only seven (two visual, three auditory and only one combined distractor). All measures of the AULA (general, visual vs. auditory, with and without distractors, and No-X and X task-specific measures) are detailed in the normative study with general population between 6 and 16 years old, recently published (Iriarte et al, 2012). Downloaded by [Temple University Libraries] at 20:51 18 November 2014 Procedure Initial recruitment took place at the Clinica Universidad de Navarra in Spain, and participants were chosen based on their medical history of ADHD symptoms as well as on the need to apply a neuropsychological evaluation exploring attentional functions.…”
Section: Differences Between Aula Nesplora (Aula) and Conners' Cpt Stmentioning
confidence: 99%
“…We can find in the literature relevant contributions addressing the study of different cognitive areas through video games and serious games, including episodic memory (Plancher et al, 2012; Sauzéon et al, 2015; Jebara et al, 2014; Díaz-Orueta et al, 2014), attention (Díaz-Orueta et al, 2014; Iriarte et al, 2016; S et al, 2014), working memory (Atkins et al, 2014; Hagler, Jimison & Pavel, 2014) and executive functions (Werner et al, 2009; Nolin et al, 2013) among others. The works referenced tackle a specific aspect of the broader topic of the introduction of games in neuroscience to detect mental disorders such as Mild Cognitive Impairment (MCI) (Nolin et al, 2013; Raspelli et al, 2011; Werner et al, 2009; Aalbers et al, 2013; Tarnanas et al, 2013; Kawahara et al, 2015; Fukui et al, 2015), Alzheimer’s Disease (AD) (Tarnanas et al, 2013; Kawahara et al, 2015; Fukui et al, 2015), Traumatic Brain Injury (TBI) (Wilson et al, 1989; Canty et al, 2014), Chronic Fatigue Syndrome (CFS) (Attree, Dancey & Pope, 2009), or Attention Deficit Hyperactivity Disorder (ADHD) (Parsons et al, 2007; Pollak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, comparison studies on different hand controllers showed that the more familiar, like mouse, keyboards, and VR controllers, provided a best performance, although the participants appreciated a more natural interaction (McMahan et al, 2010). Third, the no user isolation from real-world in AR could allow a more real experience, allowing an immediate transferring of the behavioral performance in the real-life (Dunkin et al, 2007;Seymour, 2008;Saposnik et al, 2010 Hyperactivity Disorder (ADHD) in children (Diaz-Orueta et al, 2012;Iriarte et al, 2016;Nolin et al, 2016;Pollak et al, 2009;Rizzo et al, 2000). To provide a realistic assessment environment, the virtual classroom included a typical rectangular classroom with desks, blackboard, a virtual teacher, and in which participants should perform various attentional and inhibition tasks based on the traditional Continuous Performance Task.…”
Section: Atsna: Virtual Reality and Augmented Realitymentioning
confidence: 99%
“…To provide a realistic assessment environment, the virtual classroom included a typical rectangular classroom with desks, blackboard, a virtual teacher, and in which participants should perform various attentional and inhibition tasks based on the traditional Continuous Performance Task. The results of these studies showed, on one hand, positive usability data (Rizzo et al, 2000), and, on the other, good convergent and construct validity between the performance on the virtual classroom and the traditional tests (Diaz-Orueta et al, 2012;Iriarte et al, 2016;Nolin et al, 2016), as well as, sensibility and specificity to discriminate between children with and without ADHD (Pollak et al, 2009). The most of the VR studies presented in literature are in their first stage, including small groups of participants in which the main aim is to assess the feasibility of using new technologies for the assessment.…”
Section: Atsna: Virtual Reality and Augmented Realitymentioning
confidence: 99%